Effects of vibration training combined with kinesio taping on delayed onset muscle soreness of athletes’ knee joints post-DOMS induction: a randomised controlled trial - Cheng, Liang; Jiang, Yunfei; He, Benxiang (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study aimed to investigate the effects of vibration training combined with kinesio taping on delayed onset muscle soreness (DOMS) in athletes.MethodsForty-five athletes were randomly divided into the vibration group (n = 11), kinesio group (n = 11), combined group (n = 12) and control group (n = 11) to establish DOMS models of the knee. The visual analogue scale (VAS), peak torque of knee extension (60°/s), serum interleukin-6 (IL-6) and creatine kinase (CK) were measured at baseline, immediately and 24, 48 and 72 h later.ResultsIn terms of VAS, the combined group was lower than the control group (immediately and 24 h, p < 0.05). The vibration group, kinesio group and combined group had lower VAS scores than the control group, and the vibration group and kinesio group had higher VAS scores than the combined group (48 and 72 h, p < 0.001). The IL-6 and CK levels of the vibration group, kinesio group and combined group were lower than those of the control group (immediately, 24 and 48 h, p < 0.05), but those of the vibration group and kinesio group were higher than that of the combined group (24 h, p < 0.05). The peak torque of knee extension in the combined group was higher than that in the control group (24 h, p < 0.05).ConclusionVibration training and kinesio taping can alleviate muscle pain and reduce serum IL-6 and CK concentrations and muscle strength loss caused by DOMS in athletes to varying degrees, with similar effects. Compared with single intervention, combined intervention is more effective in reducing the inflammatory response and muscle micro-injury and in reducing muscle pain and muscle strength loss. These findings provide evidence-based strategies for optimizing recovery protocols in athletic training programs.